Peran bias perilaku dalam hubungan antara literasi keuangan, karakteristik sosiodemografi dan locus of control dengan keputusan investasi saham syariah - Stefani, Ana Novika; Rahman, Taufikur (Journal of Management and Digital Business, 2023)
This study aimed to determine the effect of financial literacy, locus of control, and sociodemographic characteristics on investment decisions with behavioral bias as a mediating variable. This type of research is quantitative and involves a population of Islamic stock investors in Indonesia. The sampling technique in this study used a purposive sampling technique with a total of 100 respondents. The technique used is path analysis. The results of statistical tests show that financial literacy and locus of control affect investment decisions. Locus of control influences behavioral biases. Behavioral bias as a mediating variable can mediate locus of control on investment decisions but cannot mediate financial literacy and sociodemographic characteristics on investment decisions.